PENGARUH PENDAPATAN NELAYANAN TERHADAP PENINGKATAN EKONOMI DI DESA WEWANGRIU KECAMATAN MALILI, KABUPATEN LUWU TIMUR - Pallangan, Indah Kiding; Suardi, Suardi; Rahmawati, Rahmawati; Latang, Latang (UNIVERSITAS NEGERI MAKASSAR, 2025)
This education aims to analyze: the effect of fishermen's income on increasing economic activity. This study used a quantitative approach with a type of survey research. The subjects of this study are community residents, fishermen, while the object of this study is the fisherman program. Data collection is carried out by interview, observation, documentation methods. The technique used in data analysis is product moment correlation. Based on the results of the study, it shows that the effect of nelyan income on economic improvement in Wewangriu Village, Malili District, North Luwu Regency. The increase in fishermen has an influence on economic improvement because with the income of fishermen they can produce fish and increase the income of the community, especially the fishing community. Doubts that often arise in community members to produce fish and increase community income, especially fishing communities due to feeling income.